Triggering effect of “therapeutic MSC” - Kordium, V.A.; Irodov, D.M.; Chaikovsky, Yu.B. (Вiopolymers and Cell, 2017)
The use of MSCs as a therapeutic agent is proven to be highly successful in many cases. However, the effects obtained are often temporary, and not leading to complete recovery. The reasons of such phenomenon are discussed in the article and the concept of “triggering effects” of MSCs is substantiated. The effect consists of the fact, that signal molecules, secreted by MSCs after administration, on one hand reduce the cell damage severity, supports and heals the cells. And on the other hand, MSCs induce mobilization and activation of the own (resident) stem cells, which replace the damaged cells. The realization of the therapeutic effect depends on the presence or absence of genetically determined disorders. Використання МСК як терапевтичного препарату не завжди виявляється високоефективним. У статті аналізуються можливі причини такої дії МСК і обґрунтовується концепція їх «пускового ефекту». Він полягає в тому, що сигнальні молекули, що виділяються МСК, що вводяться в організм, з одного боку зменшують ступінь ураження клітин, підтримуючи і відновлюючи пошкоджені клітини, а з іншого - призводять до мобілізації і активації власних (резидентних) СК, що в подальшому реалізують заміщення уражених клітин. Реалізація власне терапевтичного ефекту залежить від наявності або відсутності генетично детермінованих порушень. Использование МСК в качестве терапевтического препарата не всегда оказывается высокоэффективным. В статье анализируются возможные причины такого действия МСК и обосновывается концепция их «пускового эффекта». Он заключается в том, что сигнальные молекулы, выделяемые введенными в организм терапевтическими МСК (имеют двойное действие), с одной стороны уменьшают степень поражения клеток, поддерживая и восстанавливая поврежденные клетки, а с другой – приводят к мобилизации и активации собственных (резидентных) СК, которые в дальнейшем и реализуют замещение пораженных клеток. Реализация собственно терапевтического эффекта зависит от наличия или отсутствия генетически детерминированных нарушений.